Thermal degradation and kinetics analysis of imperata cylindrica biomass / Rozalia Syqirah Amrina Mohd Rozali - Mohd Rozali, Rozalia Syqirah Amrina (Faculty of Applied Sciences, 2017)
Renewable fuel that derived from the plant biomass was the one of the good alternatives to replace the limited and non-environmentally friendly fossil fuel. The research presents the physical characteristics of Imperata cylindrica (I.c) biomass using TGA and ATR FT-IR instrument. In TGA, the degradation of biomass component such as hemicellulose, cellulose and lignin occur in two stages that release volatile components. By ATR FT-IR, the volatile components can be determine by interpreting the spectrum peak produced. In the proximate analysis, the moisture content, ash, fixed carbon and volatile matter were calculated as 9.7, 7.89, 10.47 and 71.94 weight % respectively after heated in oven and burned in furnace. While, the result that obtained from TG/DTG curve were used for the kinetic analysis of1e biomass. In this analysis two kinetic model which is Kissinger-Akihira-Sunose (KAS) and Flynn-WaIl-Ozawa (FWO) model were used to obtain the activation energy Ea. From the result, the range of activation energy for FWO model was 36.552-120.632 kJ.mol-1 and for KAS was 32.173-117.793 kJ.mol-1 were obtained. This result can be compared to the previous research to know the potential of I.c biomass as renewable fuel.